La identidad cultural en el desarrollo de los pueblos. - Sevilla Brito, Miguel Angel (2021)
This research work focuses on the problem: How to promote cultural identity in Basic Education students belonging to the towns and nationalities of the Moraspungo parish of the Pangua canton, Cotopaxi province? To respond to the problem, the following general objective is formulated: To develop a pedagogical strategy to promote cultural identity in Basic Education students belonging to peoples and nationalities, to achieve this objective a Methodology was applied with a mixed approach, and with the application of the following techniques documentary analysis, auditory narrative, visual, photographic; methods that allowed to reach the following conclusions: the determination of the theoretical and pedagogical foundations of cultural identity allowed to demonstrate that epistemology is the basis for all research, the diagnosis made to students of basic education about cultural identity has been favorable for the construction of The pedagogical strategies, the construction and partial application of pedagogical strategies to promote cultural identity, has generated the interest of district and institutional authorities for being a proposal with a different initiative, the theoretical validation of the specialists endorse the relevance and viability of the proposal and the Putting it into practice highlights the importance of fostering the cultural identity of students in the educational institution.